Legal Analysis of Patient Privacy Violation in Electronic Medical Records and its Implications for Health Data Protection in Indonesia - Mandey, Aprilia Widya (Sean Institute, 2025)
The development of information technology has brought about major changes in the healthcare system, including through the implementation of electronic health records (EHR). While this system provides efficiency in the storage and access of patient data, it also poses serious challenges regarding the protection of patient privacy. This study analyzes the legal protection of electronic medical records in Indonesia and evaluates the effectiveness of existing regulations in addressing patient data leakage. Using a normative approach, this study examines various laws and regulations such as the Personal Data Protection Law (PDP Law), the Health Law, and the Electronic Information and Transaction Law (ITE Law). The results show that although regulations are in place, implementation and law enforcement are still major obstacles in the protection of patient data. Challenges such as lack of security standards, low awareness of medical personnel, and weak supervision are barriers to effective implementation of privacy protection. Therefore, further efforts are needed to strengthen regulations, raise awareness, and implement better security technology in the management of electronic medical records in Indonesia. Thus, it is hoped that the electronic medical record system can provide optimal protection of patient privacy and increase public confidence in the digitization of health services.